2017
DOI: 10.1038/srep46763
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin provides neuroprotection in models of traumatic brain injury via the Nrf2-ARE and Nrf2-autophagy pathways

Abstract: Fucoxanthin is abundant in seaweed and is considered as a powerful antioxidant. It has been proposed to possess anti-cancer, anti-obesity and anti-diabetes effects. However, its roles in brain injury models have not been fully understood. The objective of this study was to investigate the neuroprotection of fucoxanthin in models of traumatic brain injury (TBI) and the role of the nuclear factor erythroid 2-related factor 2 (Nrf2)-antioxidant-response element (ARE) and Nrf2-autophagy pathways in the putative ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(162 citation statements)
references
References 42 publications
5
156
0
1
Order By: Relevance
“…Results showed that astaxanthin administration improved sensorimotor performance and enhanced cognitive recovery. In addition, reduction of lesion size in the cortex and expressions comparable to controls of brain-derived neurotrophic factor (BDNF), growth-associated protein-43 (GAP-43), synapsin, and synaptophysin (SYP), indicating the induction of neuronal survival and plasticity, were recorded [105].…”
Section: Carotenoidsmentioning
confidence: 97%
“…Results showed that astaxanthin administration improved sensorimotor performance and enhanced cognitive recovery. In addition, reduction of lesion size in the cortex and expressions comparable to controls of brain-derived neurotrophic factor (BDNF), growth-associated protein-43 (GAP-43), synapsin, and synaptophysin (SYP), indicating the induction of neuronal survival and plasticity, were recorded [105].…”
Section: Carotenoidsmentioning
confidence: 97%
“…The culture of mouse cortical neurons was performed according to previous studies. 17,18 In brief, mouse cortical neurons were isolated from the embryos of time-mated pregnant mice and subsequently cultured in poly-D-lysine-coated six-well dishes at a density of 1 × 10 6 cells per well. Then, the neurons were cultured in neurobasal medium (Life Technologies, USA, catalogue number: 21103049) supplemented with 2% B27 (Life Technologies, USA, catalogue number: 17504044) and 1 mmol/L glutamate (Sigma Aldrich, USA, catalogue number: G3291) at 37°C on 5% CO 2 incubator.…”
Section: Primary Culture Of Mouse Cortical Neuronsmentioning
confidence: 99%
“…based on our previous studies. 18 In brief, the sections were incubated with labelling solution containing TUNEL at 37°C for 1 hour.…”
Section: Tunel Stainingmentioning
confidence: 99%
“…Moreover, Fuol possesses various beneficial biological activities such as antioxidation [26], prevention of different types of cancers [27], and protection of central nervous system neurons [28]. Although some reports suggest that fucoxanthin could alleviate TBI-induced secondary brain injury and attenuate scopolamine-induced cognitive impairments in mice, seldom reports have claimed the role of Fuol in those brain diseases [29,30]. In particular, the effects of Fuol on neuroinflammation in microglia and neuroinflammatory-related diseases are unclear.…”
Section: Introductionmentioning
confidence: 99%